The Whitechapel Summer Show '79 : Artists Working in East London (London : Whitechapel Art Gallery, 1979)
Ainsworth, Mark ; Allin, John ; Diamond, Harry ; Eyton, Anthony ; Forster, Noel ; de Goede, Jules ; Heindorff, Michael ; Jones, Dan ; Klassnik, Robin ; Nicholas, Colin ; Perks, Jeff ; Rosenbloom, Paul ; Russell, Robert ; Vaux, Marc ; X6 Dance Space
biog., ind. tent., gr. tent. per kunstenaar
Engels
The Whitechapel Summer Show '79, Whitechapel Art Gallery, London, August 1979
boek